Robotics training to improve STEM skills of Islamic boarding school students in Batam - Eko Rudiawan Jamzuri; Hendawan Soebhakti; Senanjung Prayoga; Rifqi Amalya Fatekha; Anugerah Wibisana; Fitriyanti Nakul; H. Hasnira; Riska Analia; S. Susanto; Ryan Satria Wijaya; Ika Karlina Laila Nur Suciningtyas; Widya Rika Puspita; Eka Mutia Lubis; Adlian Jefiza; B. Budiana; Ahmad Riyad Firdaus (Universitas Muhammadiyah Malang, 2024)
One potential approach to addressing the challenges posed by the advent of Industry 4.0 and Society 5.0 is to offer robotics training. This endeavor aims to enhance students' foundational understanding of STEM (Science, Technology, Engineering, and Mathematics) disciplines. The study involved collaborating with the Pondok Pesantren Granada, an Islamic Boarding School located in Batam, to provide robotics training as community service activities. The study included 29 trainees: 15 from class XI and 7 from classes X and XII. The teaching was conducted using a combination of didactic instruction, interactive discourse, and hands-on exercises. Trainees are administered a written examination to assess their proficiency level before and after the training program. The training outcomes exhibited a significant improvement in the mean STEM proficiency of trainees, with an increase of 38.15%. Furthermore, a series of activities have been effectively implemented, resulting in trainee satisfaction ratings exceeding 50% concerning course materials, trainer, and teaching equipment. A mere 17% of the individuals undergoing training expressed dissatisfaction with the allocated time, particularly the hands-on component's duration.